Manpower Optimization and Process Efficiency Improvement at a Textile Manufacturing Company - Abdullah, Rohana; Saptari, Adi; mohamad, Nor Akramin (2010)
Manufacturing needs to constantly nurture a system that optimizes the coordination of input, process and output. The ability to fully utilize the resources especially the labor and equipment in the assembly line has always been an important factor to achieve high productivity. A textile company packaging area is a highly manual operation and the management is facing a problem finding the effective way to utilize the operators and improve the processes. Thus, productivity analysis needs to be done at this area to determine the standard time and the types of wastes occurring at this area for the purpose of improving the efficiency and effectiveness of the packaging operations. In addition, the purpose of this project is to provide the company management with recommendations on improved manpower planning and methods to perform the work by the operators. Specifically, the research has applied the Work Study method especially Process Mapping, time study with stop watch and MOST Predetermined Time Standards (PTS). Results include the operator standard time and the current utilization of the packaging operator. Based on the results, recommendations such as reducing the number of operators to improve labor utilization, sequencing of jobs and changing the methods to perform the pin packaging through scoop and sticker dispensing design were made to the management. Consequently, the outcomes of this project are advantageous for the company to improve the packing area’s productivity and for the company to be cost efficient in meeting the ever demanding customer expectation while still paying attention to the employee’s well being.